Analysis of the Performance of the Deli Serdang Public Works Service in Services Related to the Implementation of Regional Roads - Dara Lisviana (Junal Ilmu Manajemen, 2021)
This research was conducted at the Deli Serdang Public Works Department. The research objective was to determine the effect provided by the service on the performance of employees at the Public Works Agency (PU) Deli Serdang. This type of research uses correlational research, the study population is 285 employees who work at the Public Works Office (PU) Deli Serdang and the sample collection using the Slovin formula as many as 74 respondents. Sources of data using primary data and secondary data, data collection techniques using literature study, questionnaires and observations. The data analysis technique used validity and reliability tests, simple linear regression, classical assumption tests and hypothesis testing. Based on the research results indicate that partially service has a positive and significant effect on employee performance